Harassment and discrimination on the basis of gender and race/ethnicity in the FEMA workforce - Farris, Coreen (Research report, 2020)
Introduction -- Study Design and Analytic Approach -- Prevalence of Gender-Based/Sexual Equal Employment Opportunity Violations in the Past Year -- Characteristics of Gender-Based/Sexual Harassment in the FEMA Workforce -- Characteristics of Gender Discrimination in the FEMA Workforce -- Prevalence of Racial/Ethnic Civil Rights Violations -- Characteristics of Racial/Ethnic Harassment in the FEMA Workforce -- Characteristics of Racial/Ethnic Discrimination in the FEMA Workforce -- Reporting Decisions, Perceived Organizational Response to Reports, and Barriers to Reporting -- The FEMA Climate -- Next Steps for FEMA -- Appendix A: Detailed Results from the FEMA Workplace Survey -- Appendix B: The FEMA Workplace Survey Instrument -- Appendix C: Climate and Incivility Literature Review.